Dynamic Map Pathfinding Using Hierarchical Pathfinding Theta-Star (HPT*) Algorithm - Darwin, Irfan; Liawatimena, Suryadiputra (International Journal of Engineering and Emerging Technology; Vol 6 No 2 (2021): July - December 2021, 2022)
Theta-Star is an efficient algorithm that can be used to find an optimal path in a map with better performance compared to the A-Star algorithm. Combining the Theta-Star with Hierarchical Pathfinding further enhances its performance by abstracting a large map into several clusters. What this combination lacks  is  the capability to handle a dynamic element in the map. Without that capability, the agent could potentially collide with elements in the map that is  undesirable  in certain conditions, while adding that capability might reduce the pathfinding algorithm's performance. The proposed algorithm aims to provide the capability to handle dynamic elements without severe negative impact on the performance of the algorithm. The effectiveness of the proposed algorithm is verified in terms of execution time, number of nodes explored, final path length, and the number of collisions that occurred.